How Work Integration Social Enterprises Help to Realize Capability: A Comparison of Three Australian Settings. Issue 1 (2nd January 2021) - Farmer, Jane; De Cotta, Tracy; Kilpatrick, Sue; Barraket, Jo; Roy, Michael; Munoz, Sarah-Anne
Abstract: Work Integration Social Enterprises (WISEs) are a response to reconfiguring social support for disadvantaged people. Here, theory and methodology from social geography were applied, to consider capability realized in/by three Australian regional city WISEs. Data were gathered using observation and interviews with supervisors and employees. Coding identified capability, then analyzed by physicality, people, narratives and practices to explore how WISEs 'assemble' capability. Comparing across cases highlighted elements that contribute to capability realization. Evidence generated reveals features of work and organization design that might be deployed to enhance capability realization. Social geographical approaches provide insights into how social enterprises generate value.